EDUKASI LITERASI GIAT MENABUNG UNTUK MENINGKATKAN KESADARAN SISWA SEKOLAH DASAR DI DUSUN II BONTOLUGUS, DESA BALAROA, KECAMATAN DAMPAL UTARA - Moh Riski; Andhy Saputra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Community Service (KKN) activities play a crucial role in instilling positive values ​​in the younger generation, particularly elementary school students. This community service program was implemented by KKN students from Madako University, Tolitoli, in Balaroa Village, Dusun II Bontolugus, North Dampal District. The main objective of the program is to build children's awareness of the importance of saving from an early age through simple, fun, and easy-to-understand financial literacy education. The implementation method includes thematic material delivery, interactive discussions, educational games, and savings simulations using piggy banks as learning tools. The results of the program showed high student enthusiasm in participating in all series of activities, as well as an increased understanding of the benefits of saving for the future, such as learning discipline, planning desires, and preparing for long-term needs. This program is expected to foster positive habits in financial management from an early age and have a lasting impact on students, families, and the school environment.